Temporal compression of pulses from a -repetiton-rate femtosecond ytterbium laser. (August 2016) - Didenko, N.V.; Konyashchenko, A.V.; Kostryukov, P.V.; Losev, L.L.; Pazyuk, V.S.; Tenyakov, S.Yu.; Bryukhanov, V.V.
Abstract: We report the temporal compression a femtosecond ytterbium laser pulse at a pulse repetition rate of using the effect of nonlinear self-phase modulation in a gas-filled capillary. A laser pulse is compressed down to with an energy efficiency of 40%. An average radiation power at the compressor output is . At a second compression stage, the time contrast is increased and the pulse duration is reduced in the process of the second harmonic generation in a KDP crystal. The obtained pulses have a duration of at an efficiency of 35%.